Early femoral component migration: comparing the anterior and posterior approach to the hip. Issue 2 (March 2020) - Culliton, Kathryn; Louati, Hakim; Sandoval, Enrique; Gofton, Wade; Pagé, Alexandre; Gharib, Georges; Beaulé, Paul E
Purpose: Early femoral component migration is a useful indicator for identifying implants at risk of failure due to aseptic loosening. The goal of this retrospective study was to identify if anterior approach (AA) treated hips are at a higher risk of failure due to aseptic loosening caused by early migration compared to hips operated on using the traditional posterior approach (PA). Methods: A total of 388 hips were included in this study, 139 AA and 249 PA treated hips. Femoral component migration was evaluated using EBRA-FCA and radiographs were assessed for radiolucency at latest follow-up. Preoperative and 2-year clinical outcomes were reported. Results: The 1- and 2-year migration rates (mm/year), and total migration (mm) at 2-year follow-up were comparable between AA and PA hips, respectively: 0.52 versus 0.41, 0.18 versus 0.19, and 0.64 versus 0.63 (all p > 0.05). Though not statistically significant, a higher percentage of AA hips passed 2-year total migration thresholds that have been associated with aseptic loosening compared to PA hips: 25.4% versus 16.5% for 1.5 mm threshold, and 11.3% versus 4.1% for the 2.7 mm threshold. Migration was not associated with the presence of radiolucent lines. All clinical outcomes improved significantly between preoperative and 2-year follow-up. Conclusions: There was no association between the AA and any significant increase in femoral component migration. A higher percentage of AA hips exceeded the migration thresholds associated aseptic loosening; however, these stems had no other indications of instability and therefore suggests that this may be a difference in migration pattern.